Decision Support System for Tourist Attractions Recommendation in Sidoarjo Using Profile Matching Method and Analitycal Hierarchy Process Method - Yurissa Mumtaz (Universitas Trunojoyo Madura, 2020)
The problem that is often faced by tourists is choosing a tourist attraction that suits the needs that are desired, and in accordance with the budget. This study aims to facilitate tourists in determining tourist attractions that suitable with standard criteria. This research compares the Profile Matching and AHP methods in the best process of decision making, from several articles reviewed. The Profile Matching method assumes an ideal predictor variable and fits the criteria. Meanwhile, the AHP method carries out simultaneous analysis and is mutually integrated between its parameters. The results of this research answer the needs of domestic and foreign tourists in determining the desired tourist attractions as needed.